(untitled) - Dominguez, Orlando J. (Philadelphia, 2004)
The Basic Provider providers: A focus on equipment used with various ACLS skills ensures that the BLS provider can instantly recognize a piece of equipment when it is needed in an emergency; An emphasis on the sequence of ALS skills allows the BLS provider to anticipate the needs of the ALS provider in rendering patient care; Use of numerous illustrations, bulleted lists, concise tables, and a user friendly writing style makes learning and reviewing advanced concepts quick, easy and effective; Tables of the most commonly used medications are included to familiarize the basic provider with what they will encounter in the field; Glossary of key terms is included for an at a glance review of terminology; The Putting It All Together chapter includes several scenarios in which basic providers can critically look at a patient and determine what their actions would be in assisting an advanced provider; The CD-ROM provides a visual tool for the basic provider to help recognize equipment, learn the types of medications, and assist with ALS skills. Containing approximately 15 minutes of video presentations, the CD-ROM includes coverage of airway skills, cardiac monitoring, vascular access, and medication administration; Convenient spiral binding allows the book to lay flat for easy use in the classroom or clinical setting.
Keywords: Human anatomy